A deuterium NMR analysis of the structure, order, and motions of a diunsaturated acyl chain in a model bilayer. - Baenziger, John Edward. (University of Ottawa (Canada), 1989)
A procedure for the biosynthesis and subsequent isolation of a series of specifically deuteriated cis,cis-octadeca-6,9-dienoic acids (18:2$\sp{\Delta 6,9}$, referred to as isolinoleic acid) was developed and the structural and motional properties of the diunsaturated acyl chain in model bilayers were examined by $\sp2$H NMR spectroscopy. An unsaturated fatty acid auxotroph of Tetrahymena was grown with an oleic acid supplement under a variety of conditions in order to determine the optimal conditions for uptake and conversion of the supplement into isolinoleic acid. A series of eleven-litre cultures were then supplemented with oleic acid deuteriated at one of ten different positions along the chain and the corresponding deuteriated isolinoleic acids isolated and purified by argentation chromatography and HPLC. GC and TLC showed that each fatty acid preparation is greater than 95% pure and a GC-MS analysis of the fragmentation pattern of the O-(trimethylsilyl) derivative of the isolinoleate ethyl ester labelled at the C$\sb9$-C$\sb $ positions confirmed that the fatty acid is 18 carbons in length and contains two double bonds located at the C$\sb6$-C$\sb7$ and the C$\sb9$-C$\sb $ positions. The location and level of deuteriation of each labelled fatty acid was also determined by $\sp $C NMR and by comparison of the $\sp $C spectra and the retention times of the various fatty acid methyl esters on GC to those of the C$\sb9$-C$\sb $ labelled sample, the structure of each fatty acid was established. Approximately 100 milligrams of isolinoleic acid were isolated per culture and the fatty acids were deuteriated, on average, to a level of 30%. The deuteriated isolinoleic acid were esterified to form 1-palmitoyl-2-isolinoleoyl-sn-glycero-3-phosphocholine (PiLPC) and $\sp2$H NMR spectra of aqueous dispersions of each were acquired over a temperature range of 1$\sp\circ$C to 40$\sp\circ$C. The line shapes of the various powder spectra are characteristic of lipids undergoing axially symmetric motions in the bilayer and the temperature dependences of the quadrupolar splittings indicate that the acyl chain becomes more disordered and that several of the segments change their average orientation with respect to the bilayer normal, with increasing temperature. The observed splittings for the C$\sb8$ methylene segment also collapse to zero at 15$\sp\circ$C indicating that, on average, the methylene unit adopts one of four possible orientations whereby both C-$\sp2$H bonds are at the magic angle (54.7$\sp\circ$) with respect to the bilayer normal. Acquiring spectra of oriented multibilayers of ($\sp2$H$\sb2$-8$\sp\prime$) -PiLPC with proton decoupling narrowed the line widths of the deuterium signals sufficiently to allow a direct measurement of $\sp2$H-$\sp2$H dipolar coupling between the two C$\sb8$ geminal deuterons and with this additional parameter the average orientation and the associated ordering tensor of the C$\sb8$ methylene unit were defined. Based on this orientation and the ratios of the quadrupolar splitting for the two deuterons attached to each double bond, the average orientations and molecular order parameters, S$\sb{\rm mol}$, for the C$\sb6$-C$\sb7$ and the C$\sb9$-C$\sb $ double bonds were also calculated. (Abstract shortened by UMI.)
Keywords: Chemistry, Biochemistry.